The Influence of Customer Orientation and Product Innovation Capability on Customer Satisfaction Medan City Sociolla Store - Pujiastuti, Wulandari; Daulay, Aqwa Naser; Aisyah, Siti (Economics, Business, Accounting & Society Review, 2025)
The cosmetic industry in Indonesia has experienced rapid expansion and has emerged as a strategic sector contributing to national economic growth. This development is accompanied by rising consumer expectations regarding product quality, service excellence, and immersive retail experiences, particularly within modern beauty store environments. This study examines how customer orientation and product innovation capability shape customer satisfaction at the Sociolla Offline Store in Medan City. A quantitative, associative research design was employed, involving 96 purposively selected respondents, with data analyzed using multiple linear regression. The findings demonstrate that customer orientation plays a central role in elevating customer satisfaction, as reflected in the effectiveness of personalized guidance, product education, and attentive interactions offered by beauty advisors. Product innovation capability likewise contributes meaningfully to the formation of satisfaction, particularly through the presence of diverse product assortments, frequent updates, aesthetic interior design, and experiential store concepts. Statistical results further show that customer orientation constitutes the more prominent determinant, while both variables collectively account for 86.2% of the variance in customer satisfaction, underscoring the robustness of the proposed model. These results highlight the necessity for beauty retail firms to strengthen customer-centered service practices while continuously advancing innovation in product offerings and store experiences to maintain competitiveness and respond to evolving consumer expectations.